Challenges of the construction sector in the global economy and the knowledge society - García, Miguel Ángel (International Journal of Strategic Property Management, 2010)
Nowadays, the Construction Sector in the EU is one of the most relevant forces of the European economy – It represents the 10% of the total EU GDP and 7% of total employment. Nevertheless, we can define this sector as a very unstructured activity with a wide range of interactions in the value chain. In fact, we can say it's a hyper‐sector that has been demonstrating over previous decades, to be market oriented and not too much innovative. Several analyses have concluded the RTD activity in the construction Sector is quite unstructured and a lot of knowledge is produced but not recorded. In most cases, the RTD and innovation activity are focused to solve day to day problems, more than a response to an innovative policy and planned activity. Main innovations have been made in the fields of materials and machinery, and most of them could be considered as a technology transfer form other sectors. The market demand – according to economical cycles, and the financial support have been the main forces that have driven the activity of the Construction Sector. The new landscape ahead, of a global economy and a society based on technology and knowledge creation and valuation, will force this sector to be more active and structured in their RTD and innovation activity.First Published online: 18 Oct 2010